A deep learning approach to test the small-scale galaxy morphology and its relationship with star formation activity in hydrodynamical simulations - Zanisi, Lorenzo; Huertas-Company, Marc; Lanusse, François; Bottrell, Connor; Pillepich, Annalisa; Nelson, Dylan; Rodriguez-Gomez, Vicente; Shankar, Francesco; Hernquist, Lars; Dekel, Avishai; Margalef-Bentabol, Berta; Vogelsberger, Mark; et al. (Monthly notices of the Royal Astronomical Society, 2021)
ABSTRACT. Hydrodynamical simulations of galaxy formation and evolution attempt to fully model the physics that shapes galaxies. The agreement between the morpho
Advance Access publication 2020 December 16
Gesehen am 05.11.2021